Effect of HCl/γ-Al2O3 and HCl/Ni/γ-Al2O3 Catalyst on The Cracking of Palm Oil - Alda Titania Dewanti; Rismawati Rasyid; Ruslan Kalla (Jurnal Kimia Valensi, 2022)
Fuel oil has a deficit every year. Therefore, a substitute fuel is needed, which can be obtained more efficiently. One of the alternative fuels that have been widely researched is biofuel. Catalytic cracking is a method of producing biofuels such as biogasoline (C5-C9), bioavtur (C10-C15) and green diesel (C16-C22). This research aims to produce biofuels by catalytic cracking of palm oil using HCl/γ-Al2O3 and HCl/Ni/γ-Al2O3 catalysts (1, 3, 5 and 7%). The catalyst was prepared by wet impregnation and characterized by x-ray diffraction, Brunauer Emmett teller and ASTM-D664. The reaction cracking process was operated at a constant temperature of 370 °C, 50 ml volume, and 1 atm pressure. The best catalyst for cracking palm oil is HCl/Ni/γ-Al2O3 (5%) with a yield of 81%, selectivity to biogasoline at 6.41%, bioavtur at 33.81%, and green diesel at 20.33%.